2019
DOI: 10.1111/tran.12281
|View full text |Cite
|
Sign up to set email alerts
|

The fly that tried to save the world: Saproxylic geographies and other‐than‐human ecologies

Abstract: The discovery of a rare fly in a North London cemetery marks my entry point into a wider reflection on the value and significance of urban biodiversity. Using different indices of ecological endangerment, along with a critical reading of new materialist insights, this paper explores the cultural, political, and scientific significance of saproxylic (rotten wood) invertebrate communities in an urban context. The paper brings the fields of urban ecology and post‐humanism into closer dialogue to illuminate aspect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(8 citation statements)
references
References 56 publications
0
7
0
1
Order By: Relevance
“…Researchers engage relationality as an explicit conceptual and/or methodological approach, advancing thinking in the discipline (e.g. Gandy, 2019; Miller, 2018; Robertson and Ljubicic, 2019; Srinivasan, 2019; Wilson, 2019), and also as a broader empirical focus, through, for example, studies of the composition and functioning of cities, landscapes and oceans (e.g. Fredriksen, 2019; Satizábal and Dressler, 2019; Serrano-Montes et al, 2019; Tănăsescu, 2019; Wood, 2019).…”
Section: Further Questions: Political and Relationalmentioning
confidence: 99%
“…Researchers engage relationality as an explicit conceptual and/or methodological approach, advancing thinking in the discipline (e.g. Gandy, 2019; Miller, 2018; Robertson and Ljubicic, 2019; Srinivasan, 2019; Wilson, 2019), and also as a broader empirical focus, through, for example, studies of the composition and functioning of cities, landscapes and oceans (e.g. Fredriksen, 2019; Satizábal and Dressler, 2019; Serrano-Montes et al, 2019; Tănăsescu, 2019; Wood, 2019).…”
Section: Further Questions: Political and Relationalmentioning
confidence: 99%
“…This is a parallel to rural landscapes where forests evolve in response to decreased (or ceased) agrarian land use [36,55], sylvicultural management [56,57] (Figure 1), or the abandonment of villages and farmsteads [58,59]. Although rewilding is likely a common process in many urban greenspaces, resulting wild woods have been mostly reported for old cemeteries in Europe, e.g., [60][61][62][63]. As an exception, Pregitzer et al [64] recently reported successional forests in urban parks in New York City.…”
Section: Introductionmentioning
confidence: 99%
“…If a mycorrhizal fungal network continuously reproduces itself, and dying trees are gradually absorbed into their offspring, then the boundary between life and death is rendered uncertain. 54 More generally, heat is an excessive force generative in ecological and earth-atmospheric systems, ceaselessly composing, decomposing, and recomposing matter and bodies of planet earth. This calls to mind Robin Mackay's striking expression of solar excess: "Thus we can say that all forms of life are solutions to the same problem; managing the excoriating excess of solar energy which will eventually consume them in death."…”
Section: Becoming-heatmentioning
confidence: 99%